The Effectiveness of Educational Videos about PPE on Safe Working Behavior in the Coal Yard Kebunker Area - Dzaki, Muhammad Nabil; Arisandi, William; Putri, Dian Utama Pratiwi (Global Health Science Group, 2024)
Based on data on work accidents at PLN Nusantara Power, South Lampung Regency in 2021 there were 22 cases, in 2022 there were 26 cases and in 2023 there were 31 cases. The area with the most workers is the area operating coal filling equipment from the coal yard to the bunker. The aim of the research is to determine the effectiveness of educational videos about PPE on safe behavior when working in the Kebunker Coal Yard Area at PT PLN Nusantara Power UPK Sebalang District. South Lampung in 2022. This type of research is quantitative with a Pre-Experiment Design, One Group Pretest - Posttest Design approach. The time of this research is from July 1 -13, 24 at PT PLN Nusantara Power UPK Sebalang District. The population in this study were all workers in the Kebunker Coal Yard area, 35 workers, with the sample in this study being the entire population, namely 35 workers. The data analysis used is univariate and bivariate analysis. The bivariate analysis used was Wilcoxon. The conclusion is that there is the effectiveness of educational videos about PPE on safe behavior in working in the coal yard plantation area at PT PLN Nusantara Power UPK Sebalang District. South Lampung with the results of statistical tests obtained a p value of 0.000 (p value <α = 0.05). Suggestions for educational activities about PPE must be carried out every day before coming to work for at least 15 minutes then an explanation using video media about the importance of using and demonstrating the use of PPE tools which are used in the Coal Yard Kebunker Area such as communication tools, Wearpacks, Safety Shoes, Masks, Safety Helmets, Earplugs, Safety Google, Gloves are then distributed to workers so that they have the video and explain the implementation of the education.